Role of probiotics on surgical site infections in colorectal surgery - Bhasin, Mayank; Sachan, Praveendra Kumar (International Surgery Journal, 2020)
Background: Elective colorectal procedures are well known for their high rates of surgical site infections (SSI). Perioperative stabilization of microflora is a potential alternative. Usage of probiotics has significantly improved intestinal microflora and reduced infectious complications and improved surgical outcome. Methods: Observational follow-up study on 100 patients. Probiotics were given along with standard preoperative protocol and development of SSI was inspected upto 30 days. The data thus collected was subjected to descriptive analysis. Results: Colorectal malignancy was the most common indication out of which carcinoma rectum was most common comprising of 40% of the total subjects. Mean days to passage of first flatus was 3.13±1.33 days. Mean days to passage of first defecation was 4.6±1.64 days. Mean days to first solid diet was 4.42±2.02 days. Mean duration of total length of hospital stay was 14.7±8.7 days. Surgical site infections were seen in 17% of the participants of the study. Urinary tract infections were seen in 2 (2%) patients. Lower respiratory tract infections were seen in 2 (2%) patients. Anastomotic leak was present in 2 cases (2.8%) out of 70 cases. Mortality was seen in 2 (2%) cases. Conclusions: Perioperative usage of probiotics can lead to decrease in incidence of infectious complications but cannot be statistically proved due to insufficient data. Also due to early bowel functioning there is decrease in the mean hospital stay which contributed to better surgical outcome and better quality of life.